2017
DOI: 10.5530/ijopp.10.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Pregnant Women and Newborns in a Secondary Referral Health Care Setting of India

Abstract: Background: Maternal nutrition status is an important determinant of pregnancy outcomes since pre-pregnancy underweight has been traditionally considered a risk factor for adverse gestation outcomes. Objectives: The current study aims to offer updated information on the nutrition status of pregnant women and newborns to facilitate the development of health care protocols based on current knowledge. Materials and methods: The current prospective, observational study of six months descriptively assessed the nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similar results also reported from earlier study. 1,13,14 The disparity may be due to less developed infrastructures, low nutritional awareness, low access to health care, safe water, and sanitation facilities, traditional ways of farming as only means of surviving and cultural and religious influences in rural areas. In addition, lower nutritional status among rural pregnant women could be explained partly by the fact that in rural areas women are more vulnerable to early marriage and childbearing than women in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results also reported from earlier study. 1,13,14 The disparity may be due to less developed infrastructures, low nutritional awareness, low access to health care, safe water, and sanitation facilities, traditional ways of farming as only means of surviving and cultural and religious influences in rural areas. In addition, lower nutritional status among rural pregnant women could be explained partly by the fact that in rural areas women are more vulnerable to early marriage and childbearing than women in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of exclusive breast milk can optimize the growth of the baby. Factors affecting the provision of breast milk are the mothers who are supported well by the family and lactation education which can increase the mothers' knowledge, attitude and behavior to give exclusive breast milk until 6 months 3,[26][27][28][29] .…”
Section: The Effect Of Moringa Oleifera Provision On Breastfeeding Mo...mentioning
confidence: 99%
“…12 The rate of poor nutritional status among pregnant women in internally displaced person camp is alarming. 13 This has a consequence for both the mother and the unborn child, 14 studies have shown that Babies born by displaced mothers have a high risk of perinatal mortality, lower birth weights, and small for gestation age at births and suffer more complications (IMDC 2018). Nutritional status is considered as an important indicator in estimating the well being of population affected with crisis and emergency.…”
Section: Introductionmentioning
confidence: 99%